Feeding health inequality through platform-based food delivery in China - Hai Ding; Chenran Liu; Yu Xie; Jia Yu; Zhengrong Yuan (Proceedings of the National Academy of Sciences, 2026)
This study examines how the expansion of online food delivery platforms affects health inequality in China. Exploiting the staggered rollout of platforms across counties and nationally representative panel data from 2010 to 2022, we find that platform entry increases overweight among low-income individuals while reducing it among high-income individuals. This divergence operates through two channels: low-income users increase consumption of fried foods and reallocate time from cooking to sedentary leisure, whereas high-income users reduce intake of calorie-dense foods and increase physical activity. These behavioral changes accumulate into downstream health consequences affecting weight-related chronic diseases and children's overweight in low-income households. Equal access to digital convenience thus does not translate into equal health benefits, suggesting that technological diffusion may amplify health disparities.